2019
DOI: 10.1111/ijfs.14271
|View full text |Cite
|
Sign up to set email alerts
|

Bitter‐tasting hydrophobic peptides prepared from soy sauce using aqueous ethanol solutions influence taste sensation

Abstract: In this study, bitter-tasting hydrophobic peptides were prepared and purified from soy sauce using aqueous ethanol solutions and ion exchange resin, and analysed using RP-HPLC and UPLC-Q-TOF-MS/MS. Most of bitter fraction from soy sauce was obtained by treatments involving 80% ethanol and subsequent chromatographic separation. This fraction contained sixteen small peptides (molecular weight < 1000 Da; rich in hydrophobic amino acids with Lys-Pro (KP), Glu-Phe (EF), Glu-Val (EV), Asp-Leu (DL), Leu-Trp (LW) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Based on the results of basic quality, it can be speculated that a part of the salt and sugar have been precipitated with aqueous ethanol solutions of increasing concentrations. Studies by Zhu et al 17 . showed that the fraction derived from soy sauce exhibited the strongest umami taste and greatest kokumi sensation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the results of basic quality, it can be speculated that a part of the salt and sugar have been precipitated with aqueous ethanol solutions of increasing concentrations. Studies by Zhu et al 17 . showed that the fraction derived from soy sauce exhibited the strongest umami taste and greatest kokumi sensation.…”
Section: Resultsmentioning
confidence: 99%
“…60% and 80%) according to Zhu et al . method 17 . In detail, freeze‐dried SSS or SSD were firstly dissolved into 60% ethanol solution (final concentration: 30 mg solid mL –1 ), prior to mixing in a Water Bath Shaker 720 × g for 30 min and centrifugation at 4 °C and 8000 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resin is a strong separation method to purify proteins, peptide and amino acids because of its high speed and efficiency (Liu et al., 2020; Zhu et al., 2020; Zhuang et al., 2016). Anion‐exchange resin is widely used for the separation of compounds which carry a net negative charge, and it could be used to separate different proteins (Staby et al., 2000) and acidic peptides (Wilson et al., 2006).…”
Section: Introductionmentioning
confidence: 99%